Kedudukan Jaksa Sebagai Dominus Litis Dalam Melakukan Keadilan Restoratif Terhadap Tindak Pidana Penyalahgunaan Narkotika - Sa’adillah, Muhammad Hanif; Yudianto, Otto (Journal Evidence Of Law, 2023)
The aim of this composition is to examine the authority of the Prosecutor in implementing Restorative Justice for those who have committed the crime of drug abuse and are currently being held at the Lamongan District Attorney's Office. Within criminal law, there is a concept known as the Double Track System, which permits perpetrators of drug abuse to either be incarcerated or receive rehabilitation through restorative justice. Additionally, this article elucidates the legal ramifications for the Prosecutor when enacting Restorative Justice for drug abuse offenders. The research method employed in this study is normative legal research, which involves investigating legal rules, principles, and doctrines to address the legal issues at hand. The objective of normative legal research is to provide solutions to current legal problems. Restorative justice was employed by the Lamongan District Attorney when dealing with the narcotics crimes committed by M. Farid, given that the perpetrator was categorized as a non-recidivist user who met all the necessary requirements. As a result, the punishment was focused on rehabilitation, which the perpetrator willingly agreed to undergo without any external pressure.